Efektifitas Exercise Interval Training terhadap Endurance Cardiovascular pada Atlet Futsal Sayan Futsal Family Academy U-23 - Mochamad Qesha Arief; Kosasih; Qorry Armen Gemael (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This research was designed to investigate the impact of interval training on improving the aerobic endurance of SFF Academy futsal athletes. The study was initiated due to the observation that several players exhibited relatively low aerobic capacity, which contributed to decreased physical performance during matches. To address this issue, in order to conduct an experiment, the researcher used a one-group pretest–posttest design involving 20 SFF Academy athletes as participants. Aerobic endurance was measured using the Yo-Yo Intermittent Recovery Test before and after the implementation of the interval training program. The collected data were analyzed through descriptive and inferential statistical procedures, including normality and homogeneity tests. A paired sample t-test was then used to evaluate the data at a significance level of 0.05. The results showed that the mean Yo-Yo Test score improved from 14.50 in the pretest to 16.44 in the posttest. Statistical analysis confirmed that the data were normally distributed and homogeneous, and the findings of the pretest and posttest differed statistically significantly, as evidenced by a 0.000 significance level (p < 0.05). Based on these results, interval training appears to significantly improve the aerobic endurance of SFF Academy futsal athletes and is therefore appropriate to be implemented in futsal physical training programs.